Оценка агроклиматических ресурсов территории Пермского края (Географический вестник=Geographical bulletin, 2017)
Дается обоснование применяемых методов оценки агроклиматических ресурсов. В частности, с помощью биоклиматического потенциала и метода дискриминантной функции проводится оценка ресурсов тепла и влаги территории Пермского края для конкретного межфазового периода.К л ю ч е в ы е с л о в а: биоклиматический потенциал; фенологические фазы выход в трубку и колошение; базисные суммы температур; коэффициент роста; биологическая продуктивность.THE EVALUATION OF AGRO-CLIMATIC RESOURCES WITHIN THE TERRITORY OF PERM REGIONThere are basis of applicable methods are given of evaluation the agro-climatic resources.Particularly, with assistance of bio-climatic potential and the method of arotidsи function, it helps to evaluate the resources of heat and moisture of the territories ofPermregion, for the concrete period between the phases.  Key words: bio-climatic potential, phonological phases, exit to the tube and the ear formation, the basis amounts of the temperatures, factor of growth, biological efficiency.